Compability of calamus Deerratus and lactosperma secundiflorum rattan particles with ordinary portland cement (2007)
An investigation was conducted to determine the optimum water to cement ratio for a locally manufactured portland cement for use in wood composites. The effects of pre-processing and calcium chloride (CaCl2) on the compatibility of two rattan canes ( Calamus deerratus and Lacosperma secundiflorum) with cement were also assessed using the compatibility factor (CA) approach. An optimum water: cement ratio of 0.45 was obtained. Generally the two rattan species were compatible with cement. The CA factors increased with increasing levels of CaCl2 concentration (65.2% to 101.5% for C.deerratus and 71.2% to 103.5% for L. secundiflorum at 0 to 3% concentrations). Removal of the silified epidermis (pre-processing) had more significant effect (p< 0.05) on the compatibility of C. deerratus with cement than in the L. secundiflorum species. Also, the particles of the Lacosperma species were more compatible with cement than those of the Calamus species probably due to the anatomy and other variations in the two species.